Maine’s Food System: An Overview and Assessment - Beck, D.; Carleton, Nikkilee; Steinhoff, Hedda; Wallace, Daniel; Lapping, Mark (Maine Policy Review, 2011)
From an agrarian and seafaring past, Maine’s food system has seen profound changes over the past two centuries. Grain, milk, livestock, fish, potatoes, vegetables and fruits used to come from small, family farms. Today, most people in Maine don’t know where their food comes from. Many are dependent on federal, state and local “emergency food systems” such as food stamps, food pantries, and childhood nutrition programs. Food-processing facilities, distribution systems, and value-added products are in short supply. Nevertheless, Maine has a diversity and abundance of food products. In this article, the authors provide a historical overview and current analysis of Maine’s food system, highlighting encouraging trends and opportunities for the state.
Keywords: Maine; food system; food production; food processing; food distribution; CSA